Implementasi Inovasi E-Perjadin terhadap Tata Kelola Perjalanan Dinas di Lingkungan Kementerian Keuangan - Sabdono, Wilis Aji; Hutabarat, David Hotman; Sutanto, Sutanto; Pertiwi, Aditya Endah (Polytechnic of State Finance STAN, 2024)
This study aims to analyze the implementation of the electronic official travel system (e-Perjadin) innovation in the Ministry of Finance using Everett M. Rogers' diffusion of innovation theory. The e-Perjadin system was designed to enhance efficiency, transparency, and accountability in managing official travel, which was previously handled manually. A qualitative descriptive method was employed to understand the adoption process, challenges, and impacts on state financial governance. The findings indicate that e-Perjadin aligns with the attributes of innovation diffusion theory: relative advantage in efficiency and accountability, compatibility with bureaucratic reform values, complexity mitigated through training, trialability enabling system improvements, and observability of benefits such as reduced administrative time and simplified audits. However, challenges remain in user adaptation and infrastructure readiness. Recommendations include continuous training, technological infrastructure enhancements, and feature development to further improve efficiency. The success of e-Perjadin is expected to serve as a digital transformation model for other government agencies.